(untitled) (Journal of Science & Technology, 2020)
Perovskite solar cells have rapidly gained attention as a promising technology for next-generation photovoltaics due to their unique combination of low-cost fabrication, high power conversion efficiency, and tunable optoelectronic properties. However, despite significant progress in recent years, efficiency barriers continue to hinder their widespread commercialization and integration into the renewable energy landscape. In this opinionated research article, we delve into the potential of perovskite solar cells and discuss strategies to unleash their full potential by overcoming efficiency limitations. We begin by providing a comprehensive overview of the importance of renewable energy and the urgent need for efficient photovoltaic technologies. The current reliance on fossil fuels and the environmental consequences associated with traditional energy sources underscore the significance of developing sustainable alternatives. Perovskite solar cells offer a promising solution, as they can be fabricated using low-cost and scalable manufacturing techniques, allowing for large-scale deployment. Next, we explore the unique properties of perovskite materials that make them suitable for photovoltaic applications. The crystal structure of perovskites provides a favorable environment for efficient charge transport and light absorption, resulting in high power conversion efficiencies. We discuss recent advancements in perovskite device architectures, including tandem structures and multijunction designs, which have shown remarkable efficiency improvements and offer a pathway towards achieving even higher performance. To address efficiency barriers, we delve into the strategies employed to enhance the performance of perovskite solar cells. This includes compositional engineering, where the chemical composition of perovskite films is tailored to improve stability and charge transport properties. We also discuss interface engineering techniques, such as passivation layers and interfacial modifications, which have demonstrated the ability to reduce recombination losses and improve device performance. Furthermore, we examine the role of materials and device engineering in unleashing the potential of perovskite solar cells. Advanced materials, such as hole-transporting materials, electron-transporting materials, and interface modifiers, are explored for their ability to enhance charge extraction and minimize defects. We also highlight the importance of device optimization, such as the engineering of charge carrier lifetimes, thickness control, and device encapsulation, to improve stability and reliability. Despite the immense potential, several practical challenges hinder the commercial viability of perovskite solar cells. We address issues such as long-term stability, scalability, and cost-effectiveness, discussing recent developments in each area. We also provide an outlook on the commercialization prospects of perovskite solar cells and highlight the necessary steps for overcoming the remaining obstacles. In conclusion, perovskite solar cells hold great promise for next-generation photovoltaics, but efficiency barriers must be overcome to enable their widespread adoption. Through this opinionated research article, we emphasize the importance of exploring novel strategies, materials, and device engineering approaches to push the boundaries of perovskite solar cell efficiency and accelerate their commercialization, ultimately contributing to a sustainable and clean energy future.